Critical Review on Pongamia Pinnata: A Versatile Medicinal Plant - Vidhale, Deepika Kyatham; Vamshi Reddy Mora,; Sairam Pasam,; Aishwarya Kotha,; Konda, Ujwala; Narender Boggula, (Asian Journal of Pharmaceutical Research and Development, 2024)
The word herb, as used in herbal medicine, is also known as botanical medicine or as phytotherapy or phytomedicine which means a plant or plant part is used to make medicine to assist in the healing process during illness and disease. So, there are many herbal remedies individually or in combination have been recommended in various medicinal treatises for the cure of different diseases.Pongamia pinnata (L.) Pierre is a tree native to Southeast Asia. Recently, interest in Pongamia pinnatafocused on its potential as a biofuel source as its seeds contain around 40% oil. However, Pongamia pinnata has multiple applications beyond biofuel production. Pongamia pinnatacan also bring socio-economic benefits as its ability to restore degraded and contaminated land provides opportunities for local communities through novel valorisation pathways. These multiple applications have potential to form part of a circular bioeconomy in line with sustainable development goals.Pongamia pinnata has a large number of applications, and among those, its medicinal value has been recognised for decades with its roots in Ayurvedic medicine and comprehensive information on Pongamia pinnata medicinal uses, phytochemistry, and pharmacology can be found.The literature covering the multiple applications of Pongamia pinnatais vast and it is beyond the scope of this study to review it in detail.Therefore, the present review aimed to compile up to date and comprehensive information of Pongamia pinnata with special emphasis on its phytochemistry, various scientifically documented pharmacological activities, traditional and folk medicine uses alongwith its role in biofuel industry.